Intervertebral disc and vertebral endplate subchondral changes associated with Modic 1 changes of the lumbar spine: a cross-sectional study. Issue 1 (December 2017) - Nguyen, Christelle; Jousse, Marylène; Poiraudeau, Serge; Feydy, Antoine; Rannou, François
Abstract Background Modic 1 changes are usually associated with degenerative disc disease (DDD). We aimed to compare Modic 1 changes with advanced degenerative disc disease (>50%-intervertebral space narrowing [IVSN]) to Modic 1 changes with less advanced lumbar degenerative disc disease (≤50%-IVSN). Methods We conducted a cross-sectional study. The computerized MRI database from a French tertiary care hospital was searched. Patients were included if they were ≥ 18 years old and had a lumbar MRI between January 1, 2006 and January 31, 2008, that showed a Modic 1 signal at a single level. The strength of the magnet was 1.5 T. MRI were reviewed by 2 assessors. Age and gender were recorded. MRI changes involving the intervertebral disc and the vertebral endplate subchondral bone were assessed for Modic 1 signal, intervertebral space narrowing, asymmetrical degenerative disc disease, spondylolisthesis, anterior and posterior intervertebral disc herniation, and anterior and lateral osteophytes. These outcomes were compared between >50%-IVSN Modic 1 and ≤50%-IVSN Modic 1 groups. For bivariate analysis, comparisons involved nonparametric Kruskal-Wallis test for quantitative variables and nonparametric Fisher's exact test for qualitative variables. Multivariate analysis was conducted to determine factors independently associated with <50%-IVSN Modic 1 changes by backward stepwise regression. Informed consent and formal approval from Institutional Review Board is not required for this type of study. This statement was confirmed by our Institutional Review Board. Results MRI for 101 individuals were eligible. Patients' mean (SD) age was 56.6(13.4) years, and 41/101(40.6%) were men. Modic 1 were most frequently observed at L4/L5 and L5/S1 (37[36.6%] cases each). As compared with >50%-IVSN Modic 1 patients, ≤50%-IVSN Modic 1 patients were younger (mean[SD] age 51.5[14.1]vs 58.8[12.6] years, p  = 0.019), Modic 1 were more frequent at L5/S1 level (19[61.3%]vs 18[25.7%], p  = 0.001), and anterior and lateral osteophytes were less frequent (13[41.9%]vs 55[78.6%], p  < 0.001, and 11[35.5%]vs 48[68.6%], p  = 0.002, respectively). Conclusions ≤50%-IVSN Modic 1 are rather found in young men at L5/S1 level and are associated with less frequent osteophytes than >50%-IVSN Modic, while >50%-IVSN Modic 1 are rather found in older women at L4/L5 level.